The relationship between knowledge and willingness COVID-19 vaccination among adolescence, in Samarinda, Indonesia - Arif, Sitti M.; Fitriani, Dian A.; Carisma, Sagena N. (International Journal of Advances in Medicine, 2024)
Background: In 2020, infections caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are still a pandemic, including in Indonesia. Numerous efforts have been made to reduce morbidity and mortality rates caused by the virus, including vaccination. The existence of a vaccine for COVID-19 in the Indonesian community faces pros and cons. The achievement rate of vaccination, in general, is still not as expected. To accelerate vaccination, the government through the Ministry of Health has issued a circular on the acceleration of COVID-19 vaccination for children from 12-17 years old. The study aims to assess the relationship between the level of knowledge and willingness to vaccinate against COVID-19 in adolescents from 12-17 years old in Sambutan Village, Samarinda city, Indonesia. Methods: This study is observational analytic with a cross-sectional design. We took samples through online questionnaires distributed to adolescents aged 12-17 years old, in Sambutan village, Samarinda city from September to December 2021. Results: The sample was 179 people, consisting of 86 people (48.04%) male and 93 people (51.96%) female. Based on the knowledge level, 144 (80.4%) have good knowledge and 35 (19.6%) have less knowledge about vaccination. As for the willingness to vaccinate, 150 (83.8%) people are willing, and 29 (16.2%) are unwilling to be vaccinated. The analysis test, obtained p<0.001, indicating that there is a relationship between the level of knowledge and willingness to vaccinate. Conclusions: The better adolescents comprehend vaccination, then their willingness to be vaccinated is higher.